PENGARUH MORALITAS INDIVIDU DAN ASIMETRI INFORMASI TERHADAP KECURANGAN AKUNTANSI: (Studi Empiris Pada OPD Kabupaten Solok) - Sinta Permata Sari; Siska Yulia Defitri; Lili Wahyuni (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of individual morality (X1) on accounting fraud (Y), the effect of information asymmetry (X2) on accounting fraud (Y). The results showed that individual morality (X1) had negative and significant effect on accounting fraud (Y). This result is evidenced by the value of tcount = 2,427 while the value of ttable = 1,669, meaning 2,427 > 1,669 Furthermore, the significant value is 0,018 < 0,05, while Information Asymmetry (X2) has an effect on Accounting Fraud (Y). This result is evidenced by the value of tcount = 3,122 while the value of ttable = 1,669, meaning 3,122 > 1,669. Furthermore, the significance value of 0,003 <0.05. After that, Individual Morality (X1) and Information Asymmetry (X2) have a simultaneous effect on Accounting Fraud (Y). This result is evidenced by the value of Fcount = 6,119 and Ftable = 2.75, which means 6,119 > 2.75. Furthermore, the significance value of 0.004 <0.05.